Literature Review Artificial Intelligence dalam Desain Grafis: Relevansi, Ancaman, dan Adaptasi Peran Desainer - Lestari, Puji (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2026)
The rapid development of artificial intelligence (AI) has significantly influenced the creative industry, particularly in the field of graphic design. AI-based technologies such as DALL-E, Midjourney, and Canva AI enable the instant creation of visuals through text-based instructions, raising debates about the relevance of designers’ roles in the digital era. This study aims to examine how the presence of AI affects graphic design practices through three main variables: relevance, threat, and adaptation. The method employed is a literature review by analyzing five scientific articles obtained from Google Scholar and Garuda databases within the last five years. The findings reveal that AI is relevant as a creative tool that accelerates workflow and expands idea exploration. However, it also poses threats in the form of job automation, plagiarism risks, and visual homogeneity. Therefore, designers are required to adapt by enhancing conceptual skills, utilizing AI as a collaborative tool, and maintaining ethical values as well as originality in every design process.